Essential Oil Compounds in Combination with Conventional Antibiotics for Dermatology - Shivar Simbu; Ané Orchard; Sandy van Vuuren (Molecules, 2024)
Antimicrobial resistance has emerged as a significant threat to public health, prompting novel combinations comprising of natural sources such as essential oil compounds with conventional antibiotics. This study aimed to determine the possible interactions between six essential oil compounds with eight antibiotics/antifungals against six pathogens (Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Acinetobacter baumannii, Cutibacterium acnes, and Candida albicans) commonly implicated in skin infections. The minimum inhibitory concentrations (MICs) for the antibiotics and essential oil compounds were evaluated singularly and in combination using the broth microdilution assay. The fractional inhibitory concentrations (FIC) were calculated to determine the interactive profile of the combinations. The synergistic interactions (FIC ≤ 0.5) were further analysed at varying ratios and depicted on isobolograms. The toxicity of the synergistic combinations was determined using the brine shrimp lethality assay. Eight synergistic interactions were identified against the selected Gram-positive and P. aeruginosa pathogens, and the combinations also demonstrated a reduced toxicity. The combination of amoxicillin and eugenol demonstrated the lowest toxicity (LC50 = 1081 µg/mL) and the highest selectivity index (14.41) when in a 70:30 ratio. This study provides insight into the in vitro antimicrobial interactions of essential oil compounds and conventional antibiotics that can form a basis for newer therapies.